Pemberdayaan Wirausaha Mandiri Keluarga dalam Mendukung Kewirausahaan Berkelanjutan di Kelurahan Geluran Sidoarjo - Dien Ajeng Fauziah; Khoir, Fatihul; Sa'adah, Ummi; Amri, Moch. Rizky Syahputra; Lestari, L. Tri (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to analyze the empowerment of family self-employment in supporting sustainable entrepreneurship in Cemerlang Business Group, Geluran Village, Sidoarjo. Through a qualitative approach of FGDs and interviews, this research explores how families as independent business units can contribute to long-term economic stability, through sustainable practices, community involvement, and resilience in the face of economic challenges. The main results show that family entrepreneurs in Geluran have great potential in driving the local economy through the application of sustainable entrepreneurship models such as the Triple Bottom Line approach and circular economy. However, challenges in the diversity of family business structures emphasize the importance of specific and contextual approaches. This research concludes that empowering self-employed families is key in supporting sustainable economic growth, with policy recommendations that include access to financial resources, training, as well as relevant sustainability programs to strengthen family businesses. In this activity, the next empowerment hope can help in the aspects of marketing, packaging, funding, training, promotion and support from the government.